WHOSE SHAREDPLANS? SCRIPTS, COLLABORATION, AND FEMINIST AI RESEARCH - Bergmann, Rachel (AoIR Selected Papers of Internet Research, 2020)
This paper examines a network of women in AI research who together expanded the range of methodologies and disciplines usually included in AI in the 1980s and 1990s. In particular, Barbara Grosz and Candace Sidner’s concept of SharedPlans offered a way to model conversational context and collaboration in multi-agent AI environments. Drawing on archival work, interviews, conference proceedings, white papers, and departmental reports, I consider the cultural, institutional, and intellectual forces that shaped this network and their research. Using a technofeminist framework (Wajcman 2004; Haraway 1990) and borrowing from Michelle Murphy’s (2012) concept of protocol feminism, this paper examines their “feminist AI protocol.” I outline on one hand an assemblage of techniques, values, methods, and practices that illustrate a protocol rooted in community, interdisciplinarity, and care; these researchers formalized human-computer dialogue as fundamentally collaborative, grounding their approach in the diverse goals and desires of real users. I argue their philosophy of “language as action” mirrors ideas circulating in feminist and critical STS simultaneously. On the other hand, this network of researchers did so from within a particular set of cultural and epistemological parameters of their computer science departments. The research practices of this network offer an opportunity to consider the limits of any feminist AI protocol without a deeper commitment to feminist epistemologies. There remains an urgent need to reflect on how to build feminist AI technologies that make room for and include many different standpoints.